Appropriability and Market Structure in a Stochastic Invention Model - Isaac, R. Mark; Reynolds, Stanley S. (Quarterly Journal of Economics, 1988)
This research examines in the laboratory a class of game-theoretic equilibrium models of private research and development (R&D). We formulate a stochastic model of R&D investment whose predictions can be examined by using laboratory experiments. The noncooperative Nash equilibrium of our operational model yields testable predictions about the effects of appropriability and market structure on R&D. The experimental results support the hypothesis that the degree of appropriability is inversely related to R&D spending. The results strongly support the hypothesis that an increase in group size yields greater aggregate R&D. The noncooperative Nash equilibrium is shown to be a good predictor of central tendencies in the experiments.